2011
DOI: 10.3109/00048674.2010.547842
|View full text |Cite
|
Sign up to set email alerts
|

Depression in the Perinatal Period: Awareness, Attitudes and Knowledge in the Australian Population

Abstract: Awareness of postnatal depression appeared to be at a high level in the community, but both anxiety and antenatal depression were comparatively under-recognized, suggesting there is considerable scope for awareness-raising. Established risk factors for postnatal depression were not coherently recognized. Ongoing tracking of perinatal mental health literacy in Australia is likely to be valuable in assessing the impact of future public awareness efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
74
5
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(92 citation statements)
references
References 35 publications
12
74
5
1
Order By: Relevance
“…A recent review of Australian and New Zealand longitudinal studies concluded that having a previous history of depression and a poor partner relationship were the two strongest predictors of perinatal mental health difficulties [38]. In this study, some women with APD might have been suffering with depression, and thus, family support and partners' support in the management of risk of APD are crucial [39]. Strategies similar to the toolkit developed to jointly address intimate partner violence and perinatal depression by the US Department of Health and Human Services (2013) could be adopted in Australia [40].…”
Section: Specific Supports and The Management Of Risk Of Apdmentioning
confidence: 87%
“…A recent review of Australian and New Zealand longitudinal studies concluded that having a previous history of depression and a poor partner relationship were the two strongest predictors of perinatal mental health difficulties [38]. In this study, some women with APD might have been suffering with depression, and thus, family support and partners' support in the management of risk of APD are crucial [39]. Strategies similar to the toolkit developed to jointly address intimate partner violence and perinatal depression by the US Department of Health and Human Services (2013) could be adopted in Australia [40].…”
Section: Specific Supports and The Management Of Risk Of Apdmentioning
confidence: 87%
“…Few studies have explored the public’s views of perinatal mental health [28], and none have done so in Canada. The purposes of this study were to identify the public’s views regarding mental health screening and treatment in pregnant and postpartum women, and to determine factors associated with those views.…”
Section: Introductionmentioning
confidence: 99%
“…Poor support from a male partner is thought to be amenable to change [95] which suggests that there may be value in developing services in this area for new and expectant fathers.…”
Section: Psychological Factors Associated With Perinatal Healthmentioning
confidence: 99%